Sandwich panel cores for blast applications: materials and graded density - Kelly,M; Arora,H; Worley,A; Kaye,M; Del,Linz P; Hooper,PA; Dear,JP (Experimental Mechanics, 2015)
Sandwich composites are of interest in marine applications dueto their high strength-to-weight ratio and tailorable mechanical properties, but their resistance to air blast loading is not well understood. Full-scale 100 kg TNT equivalent air blast testing at a 15 m stand-off distance wasperformed on glass-fibre reinforced polymer (GFRP) sandwich panels withpolyvinyl chloride (PVC); polymethacrylimid (PMI); and styrene acrylonitrile(SAN) foam cores, all possessing the same thickness and density. Further testingwas performed to assess the blast resistance of a sandwich panel containinga stepwise graded density SAN foam core, increasing in density away from theblast facing side. Finally a sandwich panel containing compliant polypropylene(PP) fibres within the GFRP front face-sheet, was subjected to blast loadingwith the intention of preventing front face-sheet cracking during blast. Measurementsof the sandwich panel responses were made using high-speed digital image correlation (DIC), and post-blast damage was assessed by sectioning thesandwich panels and mapping the damage observed. It was concluded that allcores are effective in improving blast tolerance and that the SAN core wasthe most blast tolerant out of the three foam polymer types, with the DIC resultsshowing a lower deflection measured during blast, and post-blast visualinspections showing less damage suffered. By grading the density of the core itwas found that through thickness crack propagation was mitigated, as well asdamage in the higher density foam layers, thus resulting in a smoother backface-sheet deflection profile. By incorporating compliant PP fibres into thefront face-sheet, cracking was prevented in the GFRP, despite damage beingpresent in the core and the interfaces between the core and face-sheets.